Effect of thread profile variation on pullout and bending strength of a pedicle screw - Rosdi, Daud; Kae, W. Y.; Mas Ayu, Hassan; Shah, A. (IOP Publishing, 2021)
Pedicle screw is an important instrument in treatment of spinal degeneration or disease. However, the pedicle screw failure still occurs due to the screw loosening, fracture and pullout. There are few factors that affected the pedicle screw performance as reported by previous research but still lacking study related to the pedicle screw thread profile. Thus, the aim of this research is to investigate the effect of variation of thread pitch on the pullout and bending strength of pedicle screw. The research is carried out by constructing 3D pedicle screw models (model 1-6), importing the models into ANSYS, meshing and post processing analysis. The equivalent or Von-Mises stress used to compare the bending and pullout performance of the pedicle screws. Based on the obtained finite element analysis result, the single thread pedicle screw (model 3) has the optimum performance in bending while the model 4 is the optimum in pullout performance. While, for the dual threaded pedicle screw, the model 6 which has coarse thread pitch at screw tip is better than model 5 (fine thread). Thus, it can be conclude that both the single and dual threaded pedicle screw with coarse thread pitch has lower maximum equivalent stress than fine thread pitch, which is means it has better bending and pullout performance.